Lamb and wool provisioning ecosystem services in Southern Patagonia - Peri, Pablo Luis (2021)
In Southern Patagonia, grasslands are the principal food resource for sheep reared for meat and wool as the main provisioning ecosystem services (ES). The main objective of this study was to model lamb and wool production as provisioning ES at a regional scale using climatic, topo-graphic, and vegetation variables from sheep farms across Santa Cruz province. At a regional level, animal yield ranged from 0.25 to 0.69 g lamb/m2/yr and 0.10 to 0.19 g greasy wool/m2/yr. We used multiple regression models to produce maps of lamb and wool provisioning ES across Santa Cruz province. The model for variation of lamb production explained 96% of the variance in the data and the most significant predictor variables were temperature seasonality, normalized vegetation index (NVDI, dimensionless), and desertification index. The most important variables for the model of greasy wool production were isothermality, temperature seasonality, and NVDI, which together explained 98% of the variance. The lowest CF values of both products (lamb and wool) were located in more productive grasslands. There were differences in lamb and wool production across vegetation types with the highest values being located in more productive grasslands (0.51 g lamb/m2/yr in Nothofagus antarctica forest and 0.15 g greasy wool/m2/yr in Magellanic grass steppe and N. ant-arctica). Lamb and greasy wool yields decreased with desertification gradient due to erosion pro-cesses. The main limitation of the model is related to the data availability at landscape level, which must be improved in future studies by accounting for soil type, fertility, and soil water content. The results of lamb and wool production found in the present work assist in characterizing the provisioning ES ecosystem of livestock products in Southern Patagonia. The successful management of livestock becomes an important challenge to the commercial and policy communities to satisfy so-ciety’s need for food and wool products under sustainable grassland management.